Red scare: FBI and the origins of anticommunism in the United States, 1919-1943 - Schmidt, Regin (2004)
Abstract: The anticommunist crusade of the Federal Bureau of Investigation and its legendary director J. Edgar Hoover during the McCarthy era and the Cold War has attracted much attention from historians during the last decades, but little has been known about the Bureau's political activities during its formative years. This work breaks new ground by tracing the roots of the FBI's political surveillance to the involvement of the Bureau's predecessor, the Bureau of Investigation (BI), in the nation's first period of communist-hunting, the "Red Scare" after World War I. The book is based on the first systematic and comprehensive use of the early BI files from 1908 to 1922, which have only survived on difficult-to-read microfilms deposited in the National Archives, as well as numerous collections of personal papers. The FBI's political surveillance was not a result of popular hysteria, such as scholars used to claim, or a rational response to communist spying and the Cold War confrontation, su